A techno-economic model of mycoprotein production: achieving price parity with beef protein - Risner, Derrick; McDonald, Karen A.; Jones, Carl; Spang, Edward S. (Frontiers in Sustainable Food Systems, 2023)
Predicted famines due to population increase created an interest in the development of protein alternatives during the 1950s. Currently, a renewed interest in protein alternatives has developed as a potential strategy to decrease the environmental impact of protein production and meet the global demand for protein as the population increases. Fusarium venenatum A3/5/3, the organism used for mycoprotein production has been commercially available since the 1980s, however new fungal protein companies are currently interested in scaling up production. To aid guide efforts in this domain, we created an economic model with over 340 inputs that examines the continuous production of mycoprotein utilizing airlift bioreactors. Utilizing a sensitivity analysis, we identified critical processing inputs and then developed a user-friendly excel model that allows for the exploration of customized production scenarios for interested stakeholders. Our findings indicate that mycoprotein can be cost competitive with beef on a price per protein basis. The findings also indicate that mycoprotein may not be an economically feasible alternative for other types of commodity meats (chicken) or for inexpensive meat-derived products (pet food) that utilize offal or meat byproducts not traditionally consumed in the modern western diet.